Politics, Religion, and Pandemic: Political Discourse Analysis of Islamic Parties' Responses to COVID-19 in Indonesia - Herdiansah, Ari Ganjar; Ahmad, Noor Sulastry Yurni (Jurnal Review Politik, 2024)
This article examines the forms of politico-religious narratives constructed by Islamic parties in relation to public health support and electoral interests during the COVID-19 pandemic in Indonesia. Focusing on the United Development Party (PPP) and the Prosperous Justice Party (PKS), the study employs a political discourse analysis approach, drawing data from media reports and the parties’ official websites concerning the government’s pandemic response. The findings indicate that both PPP and PKS utilized religious narratives to provide a spiritual framework for interpreting the pandemic, which aligns with their respective political stances and electoral objectives. The PPP, with its traditionalist base and role within the governing coalition, framed the pandemic as a divine test, promoting adherence to health protocols and civil obedience with subtle criticism. In contrast, the oppositional PKS portrayed the pandemic as a disaster necessitating divine protection, while consistently criticizing the government’s handling of the crisis. The article concludes that Islamic parties’ disaster perspectives are shaped by the interplay of religious narratives and political interests.